Clinical Potential for Noninvasive Prenatal Diagnosis Through Detection of Fetal Cells in Maternal Blood - Yuditiya Purwosunu; Akihiko Sekizawa; Keiko Koide; Shiho Okazaki; Antonio Farina; Takashi Okai (Elsevier, 2006)
Fetal cells circulate in maternal blood and are considered a suitable means by which to detect fetal genetic and chromosomal abnormalities. This approach has the advantage of being noninvasive. Since the early 1990s, nucleated erythrocytes (NRBCs) have been considered good target cells for a number of techniques, including fluorescence-activated cell sorting and magnetic cell sorting, using antibodies such as anti-transferrin receptor and anti-?-hemoglobin antibodies, followed by analysis with fluorescence in situ hybridization or polymerase chain reaction. In the late 1990s, the National Institute of Child Health and Human Development Fetal Cell Isolation Study assessed the reliability of noninvasive prenatal diagnosis of fetal aneuploidy using NRBCs isolated from maternal circulation. This study revealed the limitations of NRBC separation using antibodies specific for NRBC antigens. A more recent study has demonstrated the efficiency and success of recovery of NRBCs using a galactose-specific lectin, based on the observation that erythroid precursor cells have a large quantity of galactose molecules on their cell surface. Thus, recent advances in this field enhance the feasibility of this diagnostic method. This review article focuses on various methods of detection of fetal cells within the maternal circulation, as well as the status of previous and current studies and the prospective view for noninvasive prenatal diagnosis using fetal cells from the maternal circulation.